Ecologia trófica da ictiofauna na região superior do Pantanal de Mato Grosso, Brasil. - Corrêa, Carlos Eduardo (2008)
To know spatial and temporal influence in the trophic ecology of the fish fauna, this study was conducted in two distinct sites (Chacororé pond and Cuiabá river) in pantanal superior region, Mato Grosso State, Brazil, during a hydrological cycle (March 2000 to February 2001). Thus, stomach contents of 56 species were analyzed by volumetric method (%V). The chapter I intended showed a general view of the fish fauna taxonomic composition and trophic organization, assumed that the trophic organization is the composition in guilds based on number of species. The chapter II treated of the fish fauna trophic structure, that is, the composition in abundance and biomass of each trophic guild, and finally the chapter III investigated general patterns of the niche breadth and feeding overlap to the fish fauna. The fish species were organized in eight trophic guilds: algivore, detritivore, herbivore, insectivore, invertivore, omnivore, lepidophage and piscivore, and 45% of the species not changed its guilds during all studied period, regardless of the sites and hydrological period. In general, not were found significant spatial and temporal differences in the fish fauna diet. However, in relationship to abundance and biomass of the distinct guilds significant differences were found to all spatial and temporal segments. The niche breadth and feeding overlap were generally low and null model analyses not shown evidences of food competition, corroborating thus that the fish fauna is structured in trophic guilds. These results suggest that: i) the high trophic specialization of the fishes allied with the probably food availability were the factors that allowed the support of trophic organization with small spatial and temporal influence; ii) spatial and temporal changes in abundance and biomass in the distinct trophic guilds were, in general, resulted of diet changes to several fish species, what consequently increase or decrease the importance of several trophic guilds; iii) the food partitioning resources, that is, species with some differentiation niche degree, was the main mechanism that permit the coexistence of different fish species in the studied region.